Pemberdayaan Pengrajin Tas Rajutan Berbasis Kearifan Lokal Melalui Edukasi Berkelanjutan Dan Digital Marketing - Surayanah; Yuniawatika; Khusnul Khotimah; Dhiya Nasywa; Najin Fadila Foresta (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Advances in digital technology are encouraging UMKM operators to adopt more effective marketing strategies, but artisans who create hand-knitted bags based on local traditions still face limitations in utilizing digital marketing. This study aims to enhance artisans’ ability to develop their businesses through continuous education and digital marketing guidance without compromising their local cultural identity. The method used is a descriptive quantitative approach with a pre-test and post-test design targeting hand-knitted bag artisans in Senggreng Village, Malang Regency. Data were collected using a Likert-scale questionnaire that measured four indicators: the ability to identify target markets, understand customer needs, implement integrated digital marketing, and improve profitability. The results showed improvements across all indicators: target market by 12.36%, customer needs by 3.19%, integrated marketing by 12.36%, and profitability by 5.26%. These findings indicate that continuous education combined with digital marketing based on local wisdom can strengthen marketing capacity, enhance business competitiveness, and support the sustainability of UMKM in the era of digital transformation.